Preparation and characterization of coal-based graphite from Huyan mountain anthracite by high-temperature simulation. - Gaojian Chen; Daiyong Cao; Fengchu Liao; Hongsheng He; Anmin Wang; Simai Peng (PLoS ONE)
This study systematically investigates the graphitization behavior of high-metamorphic anthracite from Huyan Mountain (Shanxi, China) under extreme thermal conditions (2100-3000 °C) through integrated experimental and microstructural analyses. Acid-washed and demineralized coal samples, with or without Fe₂O₃ catalyst, were subjected to controlled thermal treatment to evaluate structural evolution and catalytic effects. X-ray diffraction (XRD) analysis identifies a critical graphitization threshold at d002 = 0.3368 nm, beyond which interlayer spacing ceases reduction despite continued lattice refinement. Below 2700 °C, Fe₂O₃ catalysis significantly accelerates aromatic layer stacking and in-plane defect healing, advancing graphitization process. Post-threshold stabilization (≥2700 °C), both catalytic and non-catalytic systems exhibit analogous d002 stagnation, yet high-resolution transmission electron microscopy (HRTEM) reveals persistent structural ordering, including increased carbon layer stacking (up to 10 layers) and reduced edge defects. Comparative scanning electron microscopy (SEM) demonstrates enhanced flake alignment and interlayer compactness in catalyzed samples. These findings highlight intrinsic limitations in coal-derived graphite synthesis, emphasizing precursor composition as a decisive factor in graphitization potential. The work provides critical insights into graphitization mechanisms and constraints for artificial coal-based graphite production.